Government Consolidation and Economic Development in Allegheny County and the City of Pittsburgh - Archibald, Rae W. (RAND Corporation, 2008)
This report concludes that, although evidence is mixed and effects difficult to measure, consolidating the City of Pittsburgh and Allegheny County could enhance economic development by unifying leadership, improving policy direction and coordination, and sharpening economic-development initiatives. Increased collaboration with the private sector also is important, and combining only two governments still leaves the region highly fragmented.